Cement concrete admixture based on vitamin C and water glass as well as preparation method and application of cement concrete admixture
By combining vitamin C and water glass as admixtures, the shortcomings of cement concrete in terms of setting time and strength improvement are solved, and a more efficient technical effect is achieved. It is suitable for the field of building materials in construction projects, especially buildings, bridges, tunnels, road bridges, road bridges, etc.
Patent Information
- Application Number
- CN202510768400.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-10
- Publication Date
- 2025-09-12
AI Technical Summary
Existing cement concrete admixtures have limited effectiveness in regulating setting time and improving strength, and may have a negative impact on concrete performance, making it difficult to meet performance requirements in extreme climates or high-efficiency construction scenarios.
A specific proportion of vitamin C and water glass is used as an admixture to adjust the fluidity, setting time and early and late strength of concrete, optimize the microstructure and enhance durability.
Significantly improve the workability of concrete, adjust setting time, enhance early and late strength, optimize pore structure, improve construction efficiency and durability, and adapt to the needs of different construction scenarios.
Smart Images

Figure CN120622835A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete materials, and particularly relates to a cement concrete admixture based on vitamin C and water glass, and a preparation method and application thereof. Background Art
[0002] Cement concrete is widely used in modern construction projects. It is a composite material commonly used in construction, infrastructure and other fields. Its main components are cement, water and aggregates. Traditional concrete has many problems during construction and use, such as insufficient fluidity, difficult to adjust the setting time, slow early strength development and insufficient durability. These problems limit the application of concrete in complex construction environments, especially in cold climates or scenarios with high requirements for construction efficiency. Therefore, a certain proportion of admixtures will be added when necessary. According to the usage requirements of different scenarios, the performance of concrete can be changed by adjusting the mix ratio, adding admixtures or admixtures to improve strength, durability, workability, etc.
[0003] At present, common admixtures in cement concrete include water reducers, retarders, quick-setting agents, air-entraining agents, etc., which are suitable for different construction scenarios.
[0004] Specifically, sugar, phosphate, and lignin sulfonate retarders are commonly used in low-temperature environments or when long construction times are required. However, even with the addition of existing retarders, they can negatively impact cement concrete. For example, sugar and phosphate retarders are significantly affected by temperature and cement type, potentially leading to slow strength development in the cement concrete's later stages. They also require high control over the dosage, resulting in unstable results. Lignin sulfonate retarders are less effective than other retarders, can be incompatible with other admixtures, and are relatively expensive.
[0005] CN115010414A discloses an alkali-activated concrete material prepared using vitamins as admixtures. The material comprises the following raw materials by weight: 1-46 parts vitamins, 10-60 parts activator, 80-430 parts silicon-aluminum precursor, 10-436 parts gravel, 10-436 parts sand, 0-32 parts fiber, 0-20 parts chemical admixture, 0-100 parts cement clinker, and 50-420 parts water. Calculations show that water glass accounts for less than 30% of the total concrete material, acting as an activator in the formulation. Therefore, the material actually discloses an alkali-activated concrete system in which water glass acts as a salt in the reaction. The problem to be solved is to selectively adjust the setting time and compressive strength by adding VC. In particular, Example 2 shows that the setting time and compressive strength results of the five experimental groups are not proportional. That is, the group with the optimal setting time does not have the optimal compressive strength, a problem that is also common with almost all current admixtures.
[0006] Therefore, developing an admixture that can effectively improve the performance of cement concrete is of great significance to meeting the demand for high-performance concrete in modern construction projects. Summary of the Invention
[0007] The purpose of the present invention is to provide a cement concrete admixture based on vitamin C and water glass, its preparation method, and application, in order to solve at least one of the above problems, so as to address the problems that admixtures in the prior art have limited effects on the performance of cement concrete, especially fluidity, setting time, and strength, and cannot achieve simultaneous improvement of multiple properties, and existing admixtures also have negative effects on cement concrete. The cement concrete admixture proposed in this solution, based on vitamin C and water glass, can significantly improve the workability of concrete, adjust the setting time, increase the early and late strength, and enhance its durability through the combination of vitamin C and water glass in a specific ratio.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] The first aspect of the present invention discloses a cement concrete admixture based on vitamin C and water glass.
[0010] The following components are included in mass percentage:
[0011] Vitamin C powder 5-10%;
[0012] Water glass solution 40-45%;
[0013] Water balance.
[0014] Preferably,
[0015] The following components are included in mass percentage:
[0016] Vitamin C powder 6-8%;
[0017] Water glass solution 42-45%;
[0018] Water balance.
[0019] Preferably, the mass of the water is 6 to 8 times that of the vitamin C powder.
[0020] Preferably,
[0021] The composition comprises the following components in parts by weight:
[0022] 150 parts of vitamin C powder;
[0023] 900 parts of water glass solution;
[0024] 950 parts of water.
[0025] The second aspect of the present invention discloses a method for preparing a cement concrete admixture based on vitamin C and water glass as described above.
[0026] The steps include:
[0027] Weigh vitamin C powder and mix it with water, stirring at room temperature until the vitamin C powder is dissolved to obtain a vitamin C solution;
[0028] Weigh the water glass solution, add the vitamin C solution into the water glass solution, and stir at room temperature to obtain the admixture.
[0029] The third aspect of the present invention discloses an application of any of the above-mentioned cement concrete admixtures based on vitamin C and water glass in the field of construction engineering technology.
[0030] Preferably, the method of using the admixture is:
[0031] The steps include:
[0032] Add admixtures to river sand and pre-mix;
[0033] Then cement and water are added and stirred to form cement concrete.
[0034] The addition amount of vitamin C powder is 0.1-0.5% of the cement mass.
[0035] The amount of water glass solution added is 1.0-1.5% of the cement mass.
[0036] Preferably, in the admixture:
[0037] The addition amount of vitamin C powder is 0.2% of the cement mass.
[0038] The amount of water glass solution added is 1.2% of the cement mass.
[0039] The usage ratio of river sand, cement and water is not limited in this solution and is determined according to the actual concrete formula.
[0040] Preferably,
[0041] The pre-mixing time is 1 minute;
[0042] The stirring speed is 50-150 rpm, and the stirring time is 4-5 minutes.
[0043] Preferably, the admixture is added to cement concrete, and the obtained cement concrete material is used in the construction of roads and bridges.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] The admixture of this invention aims to address the problems associated with the construction and use of traditional cement concrete by optimizing key performance indicators such as concrete fluidity, setting time, and compressive strength. By combining vitamin C and water glass in a specific ratio, the admixture significantly improves concrete workability, regulates setting time, increases early and late strength, and optimizes the concrete's microstructure, enhancing its durability.
[0046] In this field, there is a certain contradiction between improving fluidity and improving compressive strength. Under normal circumstances, it is difficult to improve both at the same time. VC alone has a certain anti-coagulation ability. However, once anti-coagulation admixtures are added to concrete, its compressive strength, especially the compressive strength in the early and middle stages, will inevitably decrease. However, the admixture configured in the present invention, when added to concrete, has high fluidity in the early stage and high compressive strength in the early, middle and late stages, thus achieving a simultaneous improvement in fluidity and compressive strength. This is the core innovation of the present invention.
[0047] The admixture of the present invention can significantly improve the fluidity of concrete, optimize construction operability, reduce construction difficulty, improve construction efficiency, and the improvement of fluidity will not affect other performance indicators. At the same time, the admixture can flexibly adjust the setting time, shorten the initial setting time to speed up the construction progress, and appropriately extend the final setting time to prevent early cracking, meeting the needs of different construction scenarios. It has broad application prospects in extreme climates, rapid construction projects, and special projects with high concrete performance requirements. The optimized pore structure reduces the porosity of concrete, improves density, enhances durability, and extends service life. In addition, the admixture significantly improves the early and late compressive strength of concrete by regulating the cement hydration reaction, meeting the needs of modern construction projects for high-performance concrete.
[0048] The admixture of the present invention uses vitamin C and water glass as common materials, which are low in cost, non-toxic and environmentally friendly, and meet the requirements of sustainable development. Compared with the admixture formula disclosed in the prior art CN115010414A, the water glass in the formula of this solution accounts for 40-45%, forming a silicate system, and the pore size in the structure is reduced (the prior art CN115010414A establishes a three-dimensional aluminosilicate structure), which improves the fluidity as a whole, which is of great benefit to construction; the later strength is greater, and the concrete strength will not be affected by the problem of early fluidity; and the group with the best setting time also has the best compressive strength. Therefore, this solution provides an admixture that not only prolongs the final setting time, but also does not affect the compressive strength, and even improves the compressive strength.
[0049] By adding the admixture of the present invention to optimize the fluidity, setting time and compressive strength of concrete, an effective solution can be provided for modern construction projects, which can significantly improve construction efficiency and the long-term performance of concrete, and has significant economic and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 The particle size distribution test results of the cement concrete material obtained by adding the admixture prepared in Example 1 to cement concrete;
[0051] FIG2 shows the hydration heat test results of Test Example 1, where A shows the thermal power of hydration heat and B shows the cumulative hydration heat (Heat) changing over time;
[0052] FIG3 shows the mercury pressure intrusion test results of Test Example 1, wherein A shows the relationship between the differential intrusion amount and the pore size, and B shows the relationship between the cumulative intrusion amount and the pore size;
[0053] Figure 4 The compressive strength test results. DETAILED DESCRIPTION
[0054] The following embodiments and comparative examples are only used to more clearly illustrate the technical solutions of the present invention so that those skilled in the art can better understand and utilize the present invention, but are not intended to limit the scope of protection of the present invention.
[0055] The names and abbreviations of the test methods, production processes, instruments and equipment involved in the embodiments and comparative examples of the present invention are conventional names in the field and are very clear and unambiguous in the relevant fields of use. Those skilled in the art can understand the conventional process steps based on the names and apply the corresponding equipment, and implement them according to conventional conditions or the conditions recommended by the manufacturer.
[0056] The various raw materials or reagents used in the examples and comparative examples of the present invention are not particularly limited in their sources and are all conventional products that can be purchased commercially.
[0057] A cement concrete admixture based on vitamin C and water glass, comprising the following components in percentage by mass:
[0058] Vitamin C powder 5-10%;
[0059] Water glass solution 40-45%;
[0060] Water balance.
[0061] Preferably include the following components in mass percentage:
[0062] Vitamin C powder 6-8%;
[0063] Water glass solution 42-44%;
[0064] Water balance.
[0065] Among them, the mass of water is 6 to 8 times that of vitamin C powder.
[0066] Most preferably, the following components are included in parts by weight:
[0067] 150 parts of vitamin C powder;
[0068] 900 parts of water glass solution;
[0069] 950 parts of water.
[0070] The preparation method of the above-mentioned cement concrete admixture based on vitamin C and water glass comprises the following steps:
[0071] Weigh vitamin C powder and mix it with water, stirring at room temperature until the vitamin C powder is dissolved to obtain a vitamin C solution;
[0072] Weigh the water glass solution, add the vitamin C solution into the water glass solution, and stir at room temperature to obtain the admixture.
[0073] The above-mentioned cement concrete admixture based on vitamin C and water glass can be added into cement concrete and applied in the field of construction engineering technology, such as buildings, bridges, etc.
[0074] The method for using the admixture comprises the following steps:
[0075] Add admixtures to river sand and pre-mix;
[0076] Cement and water are then added and mixed to form cement concrete material.
[0077] The added amount of vitamin C powder is 0.1-0.5% of the mass of the cement, and the added amount of water glass solution is 1.0-1.5% of the mass of the cement.
[0078] Furthermore, the added amount of vitamin C powder is 0.2% of the mass of cement, and the added amount of water glass solution is 1.2% of the mass of cement.
[0079] The premixing time was 1 minute;
[0080] The stirring speed is 50-150 rpm, and the stirring time is 4-5 minutes.
[0081] The ratio of river sand, cement and water in this solution is not limited and is determined according to the actual concrete formula.
[0082] This admixture effectively regulates concrete's fluidity and setting time, while also improving its strength. When applied to concrete, it accelerates construction progress and reduces the risk of plastic shrinkage cracking. It is suitable for diverse construction scenarios, including road and bridge repair, tunnel support, and slope reinforcement. It provides an effective solution for modern construction projects, with significant economic and social benefits.
[0083] Example 1
[0084] Configuration of admixtures and their use in cement concrete
[0085] 1) Preparation of admixtures.
[0086] Weigh 150 g of vitamin C powder, add 950 g of water thereto, and stir with a stirrer at room temperature until the vitamin C powder is completely dissolved to form a uniform vitamin C solution.
[0087] Weigh 900g of water glass and slowly add the prepared vitamin C solution to the weighed water glass. Stir the mixture in a laboratory stirrer at room temperature for 2 minutes to ensure that the vitamin C solution and water glass are thoroughly mixed to form an admixture.
[0088] 2) Prepare cement concrete samples containing admixtures.
[0089] Add 1 kg of the prepared admixture to 9 kg of river sand at a uniform speed, and use a mixing agitator to pre-mix the admixture with the river sand for 1 minute to ensure that the admixture is evenly distributed in the river sand.
[0090] 36 kg of cement and 18 kg of water were added to the premixed river sand and stirred at 60 rpm using a mixer for 5 minutes until the mixture was completely mixed to form a cement concrete material, which was recorded as the WG+VC group.
[0091] The mixed material is quickly poured into a clean and oiled mold, and a vibration table is used to vibrate it several times to eliminate bubbles and ensure that the concrete is dense. The poured concrete sample is cured in a standard curing room.
[0092] Comparative Example 1
[0093] This comparative example is based on Example 1, but without adding vitamin C powder, and is recorded as group WG.
[0094] Comparative Example 2
[0095] This comparative example is based on Example 1, but without adding water glass, and is recorded as VC group.
[0096] Control Example
[0097] This comparative example is based on Example 1, but without adding vitamin C powder and water glass, and is recorded as the Control group.
[0098] Table 1 summarizes the dosage of components in Example 1, Comparative Examples 1, 2 and the reference example (unit: kg / m 3 , indicating the mass amount of each component in 1 cubic meter of concrete).
[0099] Table 1 The dosage of each test group (unit: kg / m 3 )
[0100]
[0101] In Table 1, * indicates that the solid content of water glass is 35%; the difference in water content among the four groups is due to the difference in the amount of water glass used to balance it.
[0102] Test Example 1
[0103] 1) Flowability test:
[0104] The fluidity test is carried out according to the ASTM C1437 standard to evaluate the workability of concrete.
[0105] The test procedure is as follows: Clean and moisten the flow table and mold. Load the mold with concrete in two layers, ramming each layer 25 times. Lift the mold vertically to allow the concrete to flow freely. Raise the flow table 15 times at a frequency of once per second. Measure the concrete expansion diameter in four different directions and take the average value. Calculate the fluidity using the following formula.
[0106] Flowability = (expanded diameter - 200 mm) / 200 mm × 100%
[0107] Table 2 shows the test results, demonstrating the fluidity of different mortar groups. The control group exhibited poor workability; the WG group exhibited improved fluidity to 62%, demonstrating that water glass improved fluidity to a certain extent; the VC group exhibited a significant increase in fluidity, demonstrating the significant improvement of vitamin C; and the WG+VC group maintained fluidity at 91%, indicating that the combination of vitamin C and WG had no negative impact and instead maintained good fluidity. Table 2 demonstrates that vitamin C and WG blend well, effectively reducing construction difficulty and improving efficiency.
[0108] Table 2 Workability (fluidity) evaluation test of cement concrete materials in each test group
[0109]
[0110] 2) Particle size distribution test:
[0111] Reasonable particle size distribution can improve the density of concrete, thereby improving its strength and durability. Refer to the standard "Particle Size Distribution-Laser Diffraction Method" (GB / T 19077-2024) for particle size distribution tests. Grind or dilute the solid sample to ensure that it is evenly dispersed. Turn on the laser particle size analyzer, set the measurement mode and parameters, and use standard substances for calibration to ensure accurate measurement results. Add the processed sample to the instrument sample pool and test it using wet measurement to ensure that the sample is evenly dispersed in the dispersant. Start the measurement program, irradiate the sample with a laser beam, capture the scattered light, and obtain a particle size distribution diagram through analysis and calculation. Perform multiple measurements, calculate the average value and relative standard deviation, evaluate the repeatability and accuracy of the measurement, and the results are as follows: Figure 1 shown.
[0112] Changes in particle size distribution may affect the strength and durability of concrete, Figure 1 The particle size distribution of the mixture is shown, reflecting the microstructure of the particles. The admixtures can be observed to optimize the concrete microstructure, improving particle cohesion and compactness. This microstructural optimization directly impacts the overall performance of concrete, particularly in terms of strength and durability.
[0113] 3) Hydration heat test:
[0114] Controlling hydration heat is a key factor in ensuring concrete's initial strength development. Hydration heat tests were conducted according to the standard "Determination of Hydration Heat of Cement" (GB / T 12959-2008). Cement samples were ground to an appropriate fineness and mixed with deionized water at a specific water-cement ratio to form a cement paste. The isothermal calorimeter was cleaned and loaded with the sample. The test program was initiated, and the instrument automatically measured and recorded the heat changes of the cement paste over a specified time period. During the test, the instrument's operating status was monitored to ensure data stability. Supporting software automatically collected and stored data, generating a hydration heat release rate curve and the hydration heat release at each age.
[0115] The changes in heat generated during the hydration process of different groups are shown in Figure 2.
[0116] Figure 2AIn the experiment, the control group showed an obvious hydration heat peak, indicating that the cement hydration reaction reached its peak at a specific time point; the addition of water glass caused the thermal power peak to be slightly delayed and the peak value was slightly lower, indicating that water glass may have slightly delayed the early hydration reaction, but the overall hydration heat release was increased, indicating that water glass had a certain accelerating effect on the overall hydration reaction; the addition of vitamin C caused the thermal power peak to be significantly reduced and the appearance time was delayed, indicating that vitamin C may have delayed the hydration reaction rate; the group with combined addition of water glass and vitamin C (WG+VC group) showed a moderate thermal power peak, and the appearance time was between the groups with separate addition of water glass and vitamin C, indicating that the combination of the two had a regulatory effect on the hydration reaction rate.
[0117] Figure 2B In the control group, the cumulative hydration heat increased linearly with time, indicating that the hydration reaction continued; the increasing rate of the cumulative hydration heat in the WG group was slightly faster than that in the control group, indicating that water glass had a certain accelerating effect on the overall hydration reaction; the increasing rate of the cumulative hydration heat in the VC group was faster than that in the control group in the early stage and slower than that in the middle and late stages, indicating that vitamin C accelerated the hydration reaction in the early stage and delayed the hydration reaction in the later stage; the increasing rate of the cumulative hydration heat in the WG+VC group was between the groups with single addition of water glass and vitamin C, further confirming the regulatory effect of the combination of the two on the hydration reaction rate.
[0118] In summary, the addition of water glass and vitamin C can regulate the hydration reaction rate of cement, thereby controlling the release of hydration heat. The addition of water glass promotes rapid development of early strength, which is important for engineering applications that require rapid strength development. The addition of vitamin C helps to slow the hydration reaction, which may contribute to the sustained development of long-term strength and durability of concrete. The combination of water glass and vitamin C provides a balanced hydration reaction regulation strategy that can accelerate early strength development while ensuring optimized long-term performance.
[0119] 4) Mercury pressure intrusion test:
[0120] Porosity has a significant impact on the strength and durability of concrete. High porosity will reduce the mechanical properties of concrete such as compressive strength and elastic modulus, and will also weaken its durability such as freeze-thaw resistance, chemical corrosion resistance and carbonation resistance. Porosity can be measured by mercury intrusion test. The mercury intrusion test is carried out in accordance with the standard "Determination of pore size distribution and porosity of solid materials by mercury intrusion and gas adsorption method" (GB / T 21650.1-2008). The test steps are as follows: take samples from the dried concrete sample, ensure that the sample surface is clean, and break about 1 cm from different areas. 3Crush the block, select a dilatometer with the appropriate volume, and load the appropriate amount of sample. Transfer the sample dilatometer to the porosimeter under nitrogen protection. Evacuate the sample dilatometer and then inject mercury. Correct the external pressure and perform low-pressure and high-pressure measurements to obtain test data. Before removing the sample dilatometer from the porosimeter, ensure that the pressure inside the instrument has dropped to atmospheric pressure and confirm by observation that the mercury has penetrated most of the sample. Figure 3A The differential intrusion volume and pore size of different groups are shown. Figure 3B Shown are the cumulative intrusion and pore size of different groups.
[0121] Figure 3A Among them, the porosity distribution of the Control group was wider, from 1nm to 10000nm, showing more pore structures; compared with the Control group, the pore volume distribution of the VC group increased significantly in the range of 1nm to 100nm, while the distribution was lower in the range of 100nm to 10000nm, indicating that the VC admixture could inhibit the formation of large pores and thus convert them into small pores; the pore volume distribution of the WG group was higher in the range of 100nm to 10000nm, indicating that the WG admixture led to the formation of large pores; compared with the Control group, the pore distribution of the WG+VC group in small pore size also increased significantly. Although the volume of small voids generated exceeded that of the VC group, its overall pore volume was significantly less than that of the Control group, showing a better pore structure optimization effect.
[0122] The cumulative intrusion volume represents the percentage of pore volume to total volume, reflecting the density of concrete. Figure 3B As shown, the total porosity of the Control group was measured to be 33.4%, and the average pore diameter was 26.1nm, indicating a higher porosity and larger average pore diameter. The total porosity of the specimens in the VC group was reduced to 29.4%, and the average pore diameter was 20.9nm, indicating that it has a significant effect on optimizing the pore structure by reducing the porosity and reducing the average pore diameter. In contrast, the porosity and average pore diameter of the specimens added with water glass were significantly higher than those of the Control group. The occurrence of this phenomenon will have a greater negative impact on the original mechanical properties of the concrete. However, the total porosity of the specimens in the WG+VC group was 31.6%, and the average pore diameter was 21.4nm, which has an optimization effect on the pore structure by reducing the porosity and reducing the average pore diameter; although it did not achieve the excellent effect of the VC group, it was also greatly improved, indicating that the composite additive has a certain synergistic optimization effect.
[0123] Mercury intrusion pressure (MIP) test results clearly demonstrate the significant impact of the admixtures in this solution on the pore structure of concrete. The addition of the admixture significantly reduces the porosity of concrete, particularly small and medium-sized pores, thereby improving the density of the concrete. Reducing porosity helps reduce the penetration of moisture and harmful substances, thereby improving the durability of concrete. The optimized pore structure helps increase the compressive strength of concrete.
[0124] Test Example 2
[0125] Comparative test with existing admixtures
[0126] Cement concrete materials with admixtures were prepared according to the method of Example 1, and a control group was set up with reference to the dosage thereof. The dosage ratios of the components were calculated as shown in Table 3, where:
[0127] The Control group was a blank control group using only cement, river sand, and water;
[0128] The molasses group is to add molasses retarder to the basic materials of cement, river sand and water;
[0129] The sodium citrate group is to add sodium citrate retarder to the basic materials of cement, river sand and water;
[0130] Fly ash group is made by adding fly ash as an admixture with increased compressive strength to the basic materials of cement, river sand and water.
[0131] Table 3 The dosage of each test group (unit: kg / m 3 )
[0132]
[0133] 1) Setting time test:
[0134] The setting time test is conducted according to the standard "Standard for Test Methods of Performance of Ordinary Concrete Mixtures" (GB / T 50080-2016): a probe is vertically penetrated into the specimen surface, and the penetration depth and resistance value are recorded. The test is repeated every 30 minutes until the penetration resistance reaches the specified value. Specifically, the specified value for initial setting time is when the penetration resistance reaches 3.5 MPa, and the specified value for final setting time is when the penetration resistance reaches 28 MPa.
[0135] The test results, shown in Table 4, show that the setting time of concrete changes after adding different admixtures. The setting time of the fly ash group was significantly affected by its capacity, resulting in delayed initial setting and early final setting, which was not conducive to flexible construction and had a disadvantage in terms of setting time. The molasses and sodium citrate groups, which have a retarding effect, had later initial setting times than the admixture group of the present invention, while their final setting times were earlier. This demonstrates that the admixtures described in the present invention can effectively and rapidly set concrete and prevent premature cracking, thereby improving construction flexibility.
[0136] Table 4 Setting time test (unit: min)
[0137]
[0138] 2) Compressive strength test:
[0139] Compressive strength tests were conducted according to the standard "Standard for Test Methods of Mechanical Properties of Ordinary Concrete" (GB / T 50081-2019). The specimen was placed at the center of the lower platen of the compression testing machine and loaded uniformly at a rate of 0.5 to 0.8 MPa / s until the specimen failed. The maximum load value was recorded. The compressive strength was calculated using the following formula:
[0140]
[0141] Among them, F is the failure load and A is the bearing area of the specimen.
[0142] During the test, the representative value of the compressive strength of a group of specimens is the arithmetic mean. If the difference between the maximum or minimum value and the middle value exceeds 15%, the middle value is taken; if both exceed 15%, the test is invalid.
[0143] Table 5 shows the changes in compressive strength at the initial and later stages of the experiment with different admixtures. The two experimental groups with the retarder had lower initial and later compressive strengths than the control group. However, the admixture group exhibited better early compressive strength than the fly ash group (an admixture that increases compressive strength), and comparable later compressive strength.
[0144] Table 5 Effect of different admixtures on compressive strength (unit: MPa)
[0145]
[0146] Combining the two tests in this embodiment, it can be seen that the admixture obtained by this solution has the functions of slowing down setting and increasing compressive strength at the same time. In terms of extending the setting time, this formula is superior to the two more common admixtures in this field, and has the construction advantages of early initial setting time and late final setting time. It can be widely used in construction scenes that need to speed up construction progress, improve early strength, reduce the impact of high temperature or dry environmental factors, and improve construction efficiency; in terms of compressive strength, the early compressive strength of this formula is better than the more common fly ash admixture in this field. This is related to the test results of early initial setting time. The later compressive strength is similar to that of fly ash, indicating that the composite of multiple materials does not have a counter-effect on the compressive strength of the admixture of the present invention, and it has a significant effect on improving the compressive strength of concrete.
[0147] Test Example 3
[0148] Reference Example 1 prepared cement concrete materials with admixtures. According to the amount of admixture added, the materials were divided into a control group (no admixture added), a 0.1% VC group, a 0.1% WG+VC group, a 0.2% VC group, a 0.2% WG+VC group, a 0.3% VC group, and a 0.3% WG+VC group. The percentage of admixture is the mass fraction of the active component in the admixture relative to the cement. For example, the 0.1% VC group indicates that the amount of VC added is 0.1% of the mass of cement, the 0.1% WG+VC group indicates that the amount of WG and VC added is 0.1% of the mass of cement, and so on. By comparing different contents of VC and WG+VC, the effects of their effects on changes in short-, medium-, and long-term compressive strength were determined.
[0149] Table 6 shows the changes in compressive strength of different groups under different curing days (3 days, 7 days and 28 days), which are plotted as bar graphs. Figure 4 As shown in the figure, the compressive strength of the control group, which did not add any admixtures, gradually increased over time, but the overall strength was relatively low. The combination of water glass and vitamin C significantly improved the compressive strength of concrete, surpassing either vitamin C or water glass alone. As the amount of water glass and vitamin C added increased, the compressive strength of concrete also increased accordingly. In particular, the combination of 0.3% water glass and vitamin C achieved the highest compressive strength at all curing time points, demonstrating the best strengthening effect.
[0150] Table 6 Compressive strength test of different concentrations of admixtures (unit: MPa)
[0151]
[0152] The above description of the embodiments is intended to facilitate understanding and use of the invention by those skilled in the art. It will be apparent that those skilled in the art can readily make various modifications to these embodiments and apply the general principles described herein to other embodiments without requiring inventive effort. Therefore, the present invention is not limited to the above-described embodiments. Improvements and modifications made by those skilled in the art based on the disclosure of the present invention, without departing from the scope of the present invention, should be within the scope of protection of the present invention.
[0153] Other ratio examples:
[0154] 1) Preparation of admixtures in different proportions.
[0155] Prepare raw materials according to the proportions shown in Table 7, weigh vitamin C powder, add water thereto, and stir with a stirrer at room temperature until the vitamin C powder is completely dissolved to form a uniform vitamin C solution.
[0156] Weigh water glass and slowly add the prepared vitamin C solution to the weighed water glass. Stir the mixture in a laboratory stirrer at room temperature for 2 minutes to ensure that the vitamin C solution and water glass are thoroughly mixed to form an admixture.
[0157] Table 7: Dosage of admixtures in different proportions
[0158]
[0159] In Table 7, the VC content and the water glass content are the contents of the corresponding substances in the admixture. As can be seen from Table 7, in other examples, only Group 3 is within the scope of the formula of this solution, and the other three groups do not meet the formula of the admixture.
[0160] 2) Prepare cement concrete samples containing admixtures.
[0161] Add 1 kg of the prepared admixture to 9 kg of river sand at a uniform speed, and use a mixing agitator to pre-mix the admixture with the river sand for 1 minute to ensure that the admixture is evenly distributed in the river sand.
[0162] Add 36 kg of cement and 18 kg of water to the premixed river sand, and use a mixer to stir at a speed of 60 rpm for 5 minutes until it is completely mixed to form a cement concrete material.
[0163] The mixed material was quickly poured into a clean and oiled mold and vibrated several times using a vibration table to eliminate bubbles and ensure that the concrete was dense. The poured concrete samples were cured in a standard curing room. The performance test results are shown in Table 8.
[0164] Table 8 Performance test of different groups of admixtures
[0165]
[0166] As shown in Table 8, Group 3 (the formulation that meets this solution) achieved the best results, achieving simultaneous improvements in fluidity and compressive strength, and possessing a relatively short initial setting time and a relatively long final setting time. Of the other three groups, only Group 4 had performance close to that of Group 3, but due to its higher water glass content, it was still relatively inferior to Group 3. Comparing Group 3 with the VC+WG group of Example 1, the performance of the two was essentially equivalent, with the VC+WG group of Example 1 slightly outperforming Group 3.
Claims
1. A cement concrete admixture based on vitamin C and water glass, characterized in that, The following components are included in mass percentage: Vitamin C powder 5-10%; Water glass solution 40-45%; Water balance.
2. A cement concrete admixture based on vitamin C and water glass according to claim 1, characterized in that, The following components are included in mass percentage: Vitamin C powder 6-8%; Water glass solution 42-45%; Water balance.
3. A cement concrete admixture based on vitamin C and water glass according to claim 1, characterized in that, The mass of the water is 6 to 8 times that of the vitamin C powder.
4. A cement concrete admixture based on vitamin C and water glass according to claim 1, characterized in that, The composition comprises the following components in parts by weight: 150 parts of vitamin C powder; 900 parts of water glass solution; 950 parts of water.
5. A method for preparing a cement concrete admixture based on vitamin C and water glass according to any one of claims 1 to 4, characterized in that: The steps include: Weigh vitamin C powder and mix it with water, and stir at room temperature until the vitamin C powder is dissolved to obtain a vitamin C solution; Weigh the water glass solution, add the vitamin C solution into the water glass solution, and stir at room temperature to obtain the admixture.
6. Use of the vitamin C and water glass-based cement concrete admixture according to any one of claims 1 to 4 in the field of construction engineering technology.
7. The use according to claim 6, characterized in that The method of using the admixture, The steps include: Add admixtures to river sand and pre-mix; Cement and water are then added and mixed to form cement concrete material.
8. The use according to claim 7, characterized in that Among the admixtures: The addition amount of vitamin C powder is 0.1-0.5% of the cement mass. The amount of water glass solution added is 1.0-1.5% of the cement mass.
9. The use according to claim 7, characterized in that Among the admixtures: The addition amount of vitamin C powder is 0.2% of the cement mass. The amount of water glass solution added is 1.2% of the cement mass.
10. The use according to claim 7, characterized in that The pre-mixing time is 1 minute; The stirring speed is 50-150 rpm, and the stirring time is 4-5 minutes.
Citation Information
Patent Citations
Alkali-activated concrete material prepared by using vitamin as additive
CN115010414A